Political dynamics hindering Africa’s economic integration: focus on the SADC region - Nyamaropa, D. (BUSE, 2020)
The African Union (AU) is persistently pursuing economic integration within the continent as evidenced by the signing of the Abuja Treaty in 1991. Southern African Development Community (SADC), as one of the regional economic communities (RECs) in Africa, signed the Trade Protocol in 1996 in order to increase the movement of goods, services and capital within the region, probably in response to the call from the AU. Regional economic initiatives are not without challenges in Africa. Thus, using the case of SADC, this study seeks to examine the political dynamics hindering Africa’s economic integration. The research argues that political dynamics of southern African states are the main challenges to a successful regional economic integration. To this end purposive sampling design was used, employing 15 total sample sizes. Its composition was from individuals with the knowledge of the research study such as social science researchers, policy makers, former government officials and others to explore hindrances to SADC’s integration. This study was conducted using in-depth interviews as the main data collection instrument. Rampant corruption, political instability, lack rule of law, colonial history and other many obstacles, were identified by the research as major internal issues derailing the region to fully implement its integration agenda. External factors such as SADC’s International Cooperating Partners (ICPs) and neo-colonialism are also acting against regionalism in SADC. The research study also discovered the initiatives that the regional body is undertaking to promote intra-SADC trade, for example, UNIVISA - which promotes the free movement of people; proposed SADC Vision 2050 and the accompanying RISDP 2020-2030 blueprint and RETOSA which centralized regional tourism. It is posited that in the interest of a sustainable and effective economic integration, SADC should include the participation of the civil society and citizens in policy making, reduce dependency on foreign aid and encourage good governance on its member states.
Keywords: Abuja Treaty; economic intergration